Plasma Neurofilament Light Chain Is Elevated in Adaptor Protein Complex 4-Related Hereditary Spastic Paraplegia - Alecu, Julian E.; Saffari, Afshin; Ziegler, Marvin; Jordan, Catherine; Tam, Amy; Kim, Soyoung; Leung, Edward; Szczaluba, Krzysztof; Mierzewska, Hanna; King, Staci D.; Santorelli, Filippo M.; Yoon, Grace; et al. (Movement Disorders, 2023)
Background: Adaptor protein complex 4-associated hereditary spastic paraplegia (AP-4-HSP) is caused by pathogenic biallelic variants in AP4B1, AP4M1, AP4E1, and AP4S1. Objective: The aim was to explore blood markers of neuroaxonal damage in AP-4-HSP. Methods: Plasma neurofilament light chain (pNfL) and glial fibrillary acidic protein (GFAP) levels were measured in samples from patients and age- and sex-matched controls (NfL: n = 46 vs. n = 46; GFAP: n = 14 vs. n = 21) using single-molecule array assays. Patients' phenotypes were systematically assessed using the AP-4-HSP natural history study questionnaires, the Spastic Paraplegia Rating Scale, and the SPATAX disability score. Results: pNfL levels increased in AP-4-HSP patients, allowing differentiation from controls (Mann-Whitney U test: P = 3.0e-10; area under the curve = 0.87 with a 95% confidence interval of 0.80–0.94). Phenotypic cluster analyses revealed a subgroup of individuals with severe generalized-onset seizures and developmental stagnation, who showed differentially higher pNfL levels (Mann-Whitney U test between two identified clusters: P = 2.5e-6). Plasma GFAP levels were unchanged in patients with AP-4-HSP. Conclusions: pNfL is a potential disease marker in AP-4-HSP and can help differentiate between phenotypic subgroups. © 2023 International Parkinson and Movement Disorder Society.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adaptor protein complex-4; biomarker; hereditary spastic paraplegia; neurofilament light; phenotypic clustering; plasma; SPG47; SPG50; SPG51; SPG52